Polypharmacy in Older Adults: The Hazard of Hospitalization and Mortality is Mediated by Potentially Inappropriate Prescriptions, Findings From the Moli-sani Study - Simona Costanzo; Augusto Di Castelnuovo; Teresa Panzera; Amalia De Curtis; Stefania Falciglia; Mariarosaria Persichillo; Chiara Cerletti; Maria Benedetta Donati; Giovanni de Gaetano; Licia Iacoviello; Licia Iacoviello; the Moli-sani Investigators (Frontiers Media S.A., 2024)
ObjectivesWe evaluated the impact of polypharmacy on the health of community-dwelling older adults.MethodsWe prospectively analyzed 5,631 individuals from the Moli-sani study (51% men, aged ≥65 years, recruitment 2005-2010, follow-up 2005-2020). Exposure was categorized as chronic polypharmacy therapy (C-PT; ≥5 therapeutic groups and >2 defined daily doses (DDDs)) or non-chronic polypharmacy therapy (NC-PT; polypharmacy but ≤2 DDDs). Hospitalization and mortality were the main outcomes. The mediating role of potentially inappropriate prescriptions (PIP) was examined.ResultsCompared to individuals not on polypharmacy, those in NC-PT and C-PT had higher hazards of mortality [21% (95% CI 7%-37%) and 30% (16%-46%), respectively] and hospitalization [39% (28%-51%) and 61% (49%-75%), respectively]. Similar results were found for cardiovascular outcomes. PIP mediated the association between polypharmacy and outcomes, with mediation effects ranging from 13.6% for mortality to 6.0% for hospitalization. Older adults without multimorbidity experienced the same harm from multiple medications as those with multimorbidity.ConclusionPolypharmacy is associated with a higher hazard of mortality and hospitalization, with PIP playing an important role. Addressing "medication without harm" requires assessing the appropriateness of drug prescriptions and monitoring for adverse effects.